ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT UNTUK MENGUKUR KINERJA KEUANGAN PADA PT. ULIMA NITRA Tbk (PERIODE 2019-2020) - Suharyadi Suhalman (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
This research aims to know the analysis of financial statements as a tool to measure the financial performance of PT. Ulima Nitra Tbk in the period of 2019 – 2020. The method used is quantitative descriptive, to understand and give a picture of the condition of the object of inspection. By using a financial proportion research strategy that covers liquidity, solubility, action, productivity and development ratios. This study uses secondary data, namely the financial report for 2019 and 2020 which has been published by the corporations in the EIB. As for the results of the research on the financial performance of PT. Ulima Nitra Tbk with the calculations of the technical analysis of the monetary proportion, it was realized that a decent rate of execution would produce a proportion of liquidity and the ratio of solubility, while an unfavourable rate of performance was seen on the activity and profitability ratio, as well as the profit growth ratio could not be calculated because financial reports only existed in the period 2019 – 2020.